Analisis Penyelesaian Perkara Ahli Waris Putusan Nomor 02/Pdt.P/2017/PA.LLG di Pengadilan Agama Lubuklinggau - Kuswoyo, Bahet Edi; Samosir, Agustinus; Fuadi, Ahmad (STAI Bumi Silampari, 2023)
This study aims to analyze the judge's consideration in the case decision Number: 02/Pdt.P/2017/PA-LLG and to find out and understand whether the case decision has fulfilled the values of justice, expediency and legal certainty. This research uses empirical normative approach methods, namely conceptual approach, statutory approach, legal history approach, comparative legal approach, then combined with approaches that are often used in empirical legal research including, sociological approach, anthropological approach, and legal psychology approach. The results showed that the basis for the judges' consideration in granting the petitioners which was the basis for considering the decision of the Lubuklinggau Class 1B Religious Court Judges in deciding the case application Number: 02/Pdt.P/2017/PA-LLG concerning the Determination of Heirs, is that the applicants are the legal heirs of the heirs of the deceased. In accordance with the Compilation of Islamic Law article 171 letter (b) The heir is a person who at the time of death or is declared dead based on the decision of the Court, leaves heirs and relics, and Heirs are people who at the time of death have blood relations or marital relations with the heir, are Muslim and are not hindered by law from becoming heirs. That the decision that has been handed down by the Panel of Judges in the case regarding the Determination of Heirs, does not meet the value of legal certainty and the values of justice, because the judge in examining and adjudicating does not carefully look at the content of positive law and does not consider aspects of justice.